2019
DOI: 10.1002/psp.2304
|View full text |Cite
|
Sign up to set email alerts
|

Migration trajectories and their relationship to mental health among internal migrants in urban China: A sequence alignment approach

Abstract: Although migration trajectories over people's life courses seem to be associated with mental health outcomes, previous studies have considered migration at only one point in time when correlating migration with mental health. However, people can migrate multiple times during their life courses. The decision to migrate can be triggered by several life course development events, such as education, entry to the labour market, marriage, or retirement. The present study addressed this research gap by focusing on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 59 publications
0
12
0
2
Order By: Relevance
“…This often increased the complexity and duration of their migration process and, therefore, the probability of stressor-exposure. To give an example, Vietnamese migrants with several stops in different countries might be more often and for a longer time confronted with an uncertain residence status and the resulting fear of rejection than those who came to Germany directly ( 37 ). Therefore, our results suggest that multiple migration experiences may enlarge the stressor load and, thereby, as previous studies with Vietnamese in Germany ( 19 ) and Sweden ( 38 ) have shown, the risk for adjustment problems and mental distress such as depression.…”
Section: Discussionmentioning
confidence: 99%
“…This often increased the complexity and duration of their migration process and, therefore, the probability of stressor-exposure. To give an example, Vietnamese migrants with several stops in different countries might be more often and for a longer time confronted with an uncertain residence status and the resulting fear of rejection than those who came to Germany directly ( 37 ). Therefore, our results suggest that multiple migration experiences may enlarge the stressor load and, thereby, as previous studies with Vietnamese in Germany ( 19 ) and Sweden ( 38 ) have shown, the risk for adjustment problems and mental distress such as depression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of sequence analysis on migration studies has begun to take off only recently. Our study joins the small but growing number of studies that use sequence analysis to examine migration patterns across substantial age ranges (di Belgiojoso & Terzera, 2018;Impicciatore & Panichella, 2019;Liao & Gan, 2020;Stovel & Bolan, 2004;Vidal & Lutz, 2018;M. Yang et al, 2020;Zufferey et al, 2021).…”
mentioning
confidence: 71%
“…For example, Impicciatore and Panichella (2019) show that different migration trajectories are associated with social mobility outcomes. M. Yang et al (2020) study internal migration trajectories in China and find that these trajectories are associated with mental health. Liao and Gan (2020) explore international migration trajectories for Filipino and Indonesian female domestic workers in Hong Kong and find that more complex migration trajectories are associated with higher job satisfaction.…”
mentioning
confidence: 99%
“…Integrated data collection that records migration decisions following a population over long periods of time is rare. Similarly to the analysis of international migrants' trajectories (Schapendonk, van Liempt, Schwarz, & Steel, 2018), there is a budding literature on internal migration trajectories and their importance (Impicciatore & Panichella, 2019; Yang, Dijst, & Helbich, 2019), but these are limited to individual subnational case studies.…”
Section: Introductionmentioning
confidence: 99%